Stainless steel railcars reduce weight, save energy. (Reprint series (Nickel Development Institute (Canada), 1992)
This brochure illustrates use of nickel containing stainless steel for light weight railcar. A lightweight stainless steel car weights about four tonnes less than one made of steel.